Formation Mechanism and Gemological Characteristics of “Yellow-Skinned” Nanhong Agate in Northeastern Yunnan, China: Evidence from Mineralogy and Geochemistry - Qiuyun Song; Shitao Zhang; Wenzhou Pu; Liurunxuan Chen; Ruohan Zuo; Xianchao Chen; Dai Zhang; Wenlian Liu (Crystals)
The “yellow-skinned” Nanhong agate represents a unique variety of Nanhong agate found in northeastern Yunnan, China, and it is highly valued for its distinctive yellow exterior and clear red–yellow interface. Owing to the limited research on this variety, the present study provides the first comprehensive analysis. Field surveys and various laboratory techniques—including polarizing microscopy, scanning electron microscopy (SEM), Fourier-transform infrared (FTIR) spectrometry, ultraviolet–visible (UV-VIS) absorption spectrometry, Raman spectroscopy, micro X-ray diffraction (µ-XRD) with Rietveld refinement, electron microprobe analysis (EPMA), and laser ablation–inductively coupled plasma mass spectrometry (LA-ICP-MS)—were utilized to investigate its gemological, microtextural, spectroscopic, and geochemical characteristics. Field surveys identified the occurrence states of the “yellow-skinned” Nanhong agate. The laboratory results indicate that the agate primarily consists of α-quartz, with minor amounts of moganite, goethite, and hematite. The coloring mechanism observed in this study is consistent with the findings of previous studies: the external yellow coloration is due to goethite, while the internal red hue is attributed to hematite. Its unique pseudo-granular silica (Type III) structure provides a foundational basis for the later formation of the “yellow-skinned” agate variety, and geochemical data reveal the distribution patterns of elements. Based on geological surveys and experimental data, the formation of the “yellow-skinned” Nanhong agate in northeastern Yunnan can be divided into two stages: first, hydrothermal fluids filled the vesicles in the Permian Emeishan Basalt Formation (P2β), leading to the formation of primary Nanhong agate. Subsequently, the Type III primary agate underwent weathering, erosion, transport, and deposition in the red–brown sandy mudstone of the Lower Triassic Feixianguan Formation (T1f). The sedimentary environment in the second stage facilitated the conversion of outer hematite into goethite, resulting in the distinct “yellow-skinned” appearance with a clear red–yellow boundary. Based on the occurrence and stratigraphic relations, this study constrains the formation age of the “yellow-skinned” Nanhong agate to approximately 261.6 Ma.